2014
DOI: 10.14740/jnr285w
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Basic Features of Electroencephalography in Metabolic Encephalopathies

Abstract: Background:The comparison of the electroencephalography (EEG) data with the patients' primary diagnosis and the relationship with the prognosis was assessed with this study in the cases that are being followed up with the diagnosis of metabolic encephalopathy (ME).Methods: A total of 306 patients who were being followed up due to ME between January 2009 and September 2011 were included in the study. The etiologic causes in the cases were detected as hyponatremia in 26.2%, hypoxic ischemic encephalopathy in 23.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Gadewar et al (31) showed that frontal and fronto-temporal sharp wave transients were reoresented as the stage of CKD was progressed and were present in stage 5 and stage 4, frontal sharp wave transients were reported in 50% of stage 5 and in 71.43% of stage 4. Demir et al (32) reported that bilateral spike wave activity was found in 14% of patients with uremic encephalopathy who don't have seizures. Also, Koçer et al (33) demonstrated that sharp wave transients in the later stages of CKD, and occipital sharp wave transients were found in stage 4 and p-value is reported to be signi cant in the distributional pattern at different progressive stages of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Gadewar et al (31) showed that frontal and fronto-temporal sharp wave transients were reoresented as the stage of CKD was progressed and were present in stage 5 and stage 4, frontal sharp wave transients were reported in 50% of stage 5 and in 71.43% of stage 4. Demir et al (32) reported that bilateral spike wave activity was found in 14% of patients with uremic encephalopathy who don't have seizures. Also, Koçer et al (33) demonstrated that sharp wave transients in the later stages of CKD, and occipital sharp wave transients were found in stage 4 and p-value is reported to be signi cant in the distributional pattern at different progressive stages of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of major organs like kidneys, liver, lungs, and the respiratory system may result in a general deterioration of the brain function. This type of secondary impairment of the brain due to the malfunctioning of other organs is called “metabolic encephalopathy” [ 18 ]. We have compared the energies of the subbands, which were obtained using DWT, with that of normal and classified using support vector machine (SVM).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Koçer et al, [26] found sharp wave transients in the later stages of CKD, occipital sharp wave transients is noted in stage 4 and p-value is found to be significant in the distributional pattern at different progressive stages of CKD. Demir et al [21] found bilateral spike wave activity in 14% of the patients with uremic encephalopathy who clinically don't have seizures and in 20% triphasic waves can be encountered in direct proportion of blood urea level. Arnold and Krishnan,[25] added that triphasic sharp waves on EEG are considered a specific feature of metabolic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%